Cultural change and population dynamics during the Bronze Age: Integrating archaeological and palaeoenvironmental evidence for Schleswig-Holstein, Northern Germany. (October 2019) - Kneisel, Jutta; Dörfler, Walter; Dreibrodt, Stefan; Schaefer-Di Maida, Stefanie; Feeser, Ingo
In archaeology, change in material culture is viewed as indicating social or cultural transformation and is the basis of our typo-chronological classification of phases and periods. The material culture from northern Germany reveals both quantitative and qualitative changes during the Bronze Age. At the same time, there is also evidence for 'boom and bust' cycles in population density/size, as indicated by changing human impact on the environment in several Bronze Age palaeoenvironmental records. These demographic fluctuations may relate to the observed changes in social phenomena in aspects of ideology, technology, food production and habitation. For example, innovations in food production, such as the adoption of new crops and agricultural techniques, could have led to population growth. While usually viewed by archaeologists as a 'negative' development, population stress or collapse may have favoured the emergence of new cultural phenomena. In order to test the cause-and-effect relationship between population dynamics and sociocultural change, we synthesise the archaeological evidence – qualitative and quantitative information from settlements, deposition finds (hoards), burials, material culture and architectural remains – for the Bronze Age in northern Germany, mainly Schleswig-Holstein, and compare it with the boom and bust pattern seen in the palaeoenvironmental record. The synchronicity of changes at ca. 1500 BC and ca. 1100 BC reflects the relationship between phases of major sociocultural transformation in the archaeological datasets and booms and busts in the palaeoenvironmental record of the region seen as a proxies for palaeo-demography. This sets the stage for a better understanding of the transformation of practices and relationships in the Bronze Age communities of the region.